Dynamics of the COVID-19 pandemic in Lebanon between 2020 and 2022 - Issa, Khouloud; Sultan, Rabih (Frontiers in Physics, 2024)
We carry out an evolutionary study of the COVID-19 pandemic, focusing on the case of Lebanon. The disease spread exhibits four eruption phases or waves. Chaos theory tools point toward a correlation of events, essentially obeying a quasi-deterministic chaotic regime. The analysis of the time series yields a largest Lyapunov exponent of 0.263, indicative of a chaotic trend. The review of past and recent analyses and modeling of pandemics could assist in the predictabilty of their course of evolution, effective management and decision making for health authorities.